Recombinant human GLP-1 beinaglutide regulates lipid metabolism of adipose tissues in diet-induced obese mice - Feng Zhang (Elsevier, 2021)
Summary: GLP-1 analogs are a class of glucose-lowering agents with multiple benefits in diabetes, but its role in adipose tissues remains to be elucidated. The aim of this study was to determine the action of recombinant human GLP-1 (rhGLP-1) Beinaglutide (BN) in the insulin sensitivity and lipid metabolism of adipose tissues. We have shown that, after BN injection, obese mice displayed lower body weight, fat mass, and plasma lipid levels. In addition, BN promoted the insulin sensitivity in the white adipose tissues. Furthermore, we have found that the BN treatment caused significant changes in content and composition of different lipid classes, including glycerolipids, glycerophospholipids, and sphingolipids, as well as expression of genes in lipid metabolic pathways in the adipose tissues. Taken together, our data demonstrate that BN could resist HFD-induced obesity by targeting the composition of major lipid classes and the expression of genes in lipid metabolism of adipose tissues.